Gendered aspects of activation policies: the limits of welfare to work - Conaghan, J (Foundation for Law, Justice and Society, 2009)
The current UK government has invested heavily in labour market activation, both as an economic and social strategy. This has resulted in the phased introduction of significant changes to welfare provision, operating alongside other activation-based initiatives, including a high-profile skills agenda, a national childcare strategy, and ‘family-friendly’ employment policies to smooth the path to paid work for those with family responsibilities. This policy brief argues that the pursuit of activation policies, particularly in the United Kingdom, is insufficiently attentive to issues of gender and to the closely related and complex nexus of gender, work, and care. The brief takes as its focus the UK government’s welfare reform programme, concentrating on those aspects in which gender considerations are, or should be, of most significance. By so doing, it also seeks to contribute to the wider debate about the desirability and effectiveness of welfare-to-work policies.